Pengenalan Multimedia Komputer untuk Pembuatan Sabun Cuci Cair: Introduction to Computer Multimedia for Liquid Soap Making' - Uminingsih; Joko Triyono3; harmastuti (JNANADHARMA, 2024)
The AL Islam Orphanage or TAYP FAMIYA (Al-Islam Foundation Orphanage for the Poor Orphans) is an orphanage for boys and girls located in the Tambak Bayan area, Depok. This orphanage also functions as a social foundation. Apart from the education provided by the orphanage, it also provides skills to provide provisions for later life. These include making liquid soap and making videos. In this article, an Introduction to Computer Multimedia is introduced to create video tutorials. In compiling computer multimedia, images, text, audio are needed which will ultimately be composed of video tutorials. The data used here is photo, video shooting about the process of making liquid soap, for editing the data that has been input using a video editor from Windows. The result of the training is a simple video of the process of making liquid soap.